2019
DOI: 10.1186/s40645-019-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of meteoric diagenesis on the geochemical composition and microstructure of Pliocene fossil Terebratalia coreanica and Laqueus rubellus brachiopod shells from northeastern Japan

Abstract: Stable carbon (δ 13 C) and oxygen isotope (δ 18 O) compositions of fossil brachiopod shells can be used to interpret paleoclimatic and paleoceanographic conditions. However, the initial isotopic composition of the living shells might be modified by diagenetic alteration. To assess the degree of this modification, we analyzed δ 13 C and δ 18 O and three common indicators of alteration in shells: minor element (manganese (Mn), iron (Fe), and strontium (Sr)) concentrations; cathodoluminescence (CL)/non-luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…The minor element concentrations of the brachiopod shell show values of 3,700 ppm for Mg, 3,000 for Sr, 0–10 for Mn, and 1,100 for Fe. The Mn values correspond with the Mn values of 0–70 (Ullmann, Frei, Korte, & Lüter, 2017), 4–30 (Lee et al, 2004); Fe values of 30–1,100 ppm reported for modern brachiopod shells and Sr values of 730–1,100 ppm (Fujioka et al, 2019) for fossil brachiopod shells. Because the Sr concentration for modern brachiopod shells (810–1,100 ppm) remain fairly constant in their fossilized counterparts, the Sr is not likely to be a good indicator of diagenetic alteration in brachiopod shells (Fujioka et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The minor element concentrations of the brachiopod shell show values of 3,700 ppm for Mg, 3,000 for Sr, 0–10 for Mn, and 1,100 for Fe. The Mn values correspond with the Mn values of 0–70 (Ullmann, Frei, Korte, & Lüter, 2017), 4–30 (Lee et al, 2004); Fe values of 30–1,100 ppm reported for modern brachiopod shells and Sr values of 730–1,100 ppm (Fujioka et al, 2019) for fossil brachiopod shells. Because the Sr concentration for modern brachiopod shells (810–1,100 ppm) remain fairly constant in their fossilized counterparts, the Sr is not likely to be a good indicator of diagenetic alteration in brachiopod shells (Fujioka et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…Because of more solubility of Mn (Post, 1999), the silicate weathering provides a significant source of Mn to both the surface and ground waters, and in cases of high concentrations of soluble Mn, it can substitute for Ca in authigenic carbonates (Johnson, Webb, Ma, & Fischer, 2016). The higher concentration of Mn in the Shinawari Formation is explained by the near surface dissolution of carbonates by weathering (probably karst), leading to enrichment of Mn oxides and carbonates (with palaeosols) having some siliciclastic input (Fujioka, Takayanagi, Yamamoto, & Lryu, 2019). Alternatively, the Mn could be as a result of the anoxic conditions, as beds are bounded by organic‐rich horizons (Figure 3f), capable to concentrate the soluble Mn (II) to high levels, similar to the Proterozoic carbonates with anoxic platforms (Holland, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Such shell material cannot be fully cleaned during manual preparation and always contains admixtures of calcite cements. The impact of the puncta-filling cement on oxygen isotope composition of the entire brachiopod shells may be considerable, providing that its δ 18 O values are at least one order of magnitude lower that those of the surrounding shell, which is possible in the case of freshwater alteration [107]. Due to the lack of other fossils in certain intervals or locations, terebratulid oxygen isotope data are, however, taken into account in many cases (e.g.…”
Section: Mn (Ppm) Fe (Ppm) Sr (Ppm)mentioning
confidence: 99%
“…Instead, iron and manganese contents were analysed for most of the used specimens, which also allow an evaluation of preservational quality (e.g., Veizer, 1980, 1981;Price and Sellwood, 1997;Wierzbowski and Joachimski, 2007;Wierzbowski et al, 2009;Fujioka et al, 2019). Since concentrations of both elements are relatively low in pristine shells, cut-off values can be defined which may be used to separate potentially altered samples from the 7 database.…”
Section: Preservation Of the Fossil Materialsmentioning
confidence: 99%